Land in PMNA KA. BPN 21 of 2020 Concerning Handling of Settlement of Land Cases in Land Registration - Reni Suryani; Eliana (Formosa Journal of Sustainable Research, 2022)
The land registration that is carried out does not guarantee that the names registered in the land book cannot be disputed if the registered name is not the real owner. The land registration activity produces a certificate of land rights, has a function for the owner and cannot be replaced. One of the functions of a certificate is as a powerful means of proof. Land registration aims to provide guarantees of legal certainty known as Rechts Cadaster/Legal Cadaster. the guarantee of legal certainty to be realized in this land registration includes certainty of the status of the registered rights, certainty of the subject of rights, and certainty of the object of rights. This land registration produces a certificate as proof of his rights. Legal certainty refers to the enactment of laws that are clear, permanent, consistent and consistent, the implementation of which cannot be influenced by subjective circumstances. Certainty and justice are not just moral demands, but factually characterize law. A law that is uncertain and does not want to be fair is not just a bad law